High coverage H2 adsorption and dissociation on fcc Co surfaces from DFT and thermodynamics. (15th March 2018) - Yu, Mengting; Liu, Lili; Wang, Qiang; Jia, Litao; Hou, Bo; Si, Yubing; Li, Debao; Zhao, Yi
Abstract: Hydrogen adsorption, desorption and dissociation on the Co(100), (311), (111) and (110) surfaces at different coverage have been systematically studied using density functional theory and ab initio atomistic thermodynamics. On the basis of the computed stepwise H2 adsorption energies, the saturated coverage on the Co(311), (111), (110) surfaces are 8/18, 3/9 and 6/18 ML, respectively, revealing that these surfaces have different potential hydro-treating abilities and activity. The lateral repulsive interactions can affect the adsorption structures and become stronger with the increasing of H2 coverage, which lead to H2 migration over Co surfaces. Comparison of dissociation energies and corresponding desorption energies, it can be concluded that H2 molecules prefer dissociation rather than desorption both kinetically and thermodynamically at different coverage. Hydrogen stable coverage on the surfaces highly depends on temperatures and H2 partial pressure. These results should provide important information about morphology of Co-catalysts under Fischer-Tropsch synthesis reduction conditions. Graphical abstract: Highlights: Coverage dependent H2 adsorption and dissociation on Co surfaces are systematically calculated. The lateral repulsive interaction can affect the H2 adsorption structures and adsorption energies. H2 dominantly exists in the form of H atoms on cobalt surfaces under Fischer-Tropsch synthesis conditions. H2 desorption temperatures on Co surfaces can be predicted.